Dopamine Modulation of Perisomatic and Peridendritic Inhibition in Prefrontal Cortex - Gao, Wen-Jun; Wang, Yun; Goldman-Rakic, Patricia S (The Journal of neuroscience, 2003)
The computations underlying cognitive functions are performed by a diversity of interactions between interneurons and pyramidal neurons that are subject to modulatory influences. Here we have used paired whole-cell recording to study the influence of dopamine on local inhibitory circuits involving fast-spiking (FS) and non-FS cells, respectively. We found that dopamine depressed inhibitory transmission between FS interneurons and pyramidal neurons but enhanced inhibition between non-FS interneurons and pyramidal cells. FS inhibitory transmission exhibited properties associated with presynaptic action at D 1 receptors that were not evident in non-FS inhibitory connections. In addition, FS and non-FS interneurons differed morphologically, forming contacts on the perisomatic and peridendritic domains, respectively, of their pyramidal cell targets. These findings provide evidence for both a dual mode of inhibition in prefrontal circuitry and circuit-dependent modulation by dopamine.